Global nutritional equity of fishmeal and aquaculture trade flows - Laura G. Elsler; Jessica A. Gephart; Jessica Zamborain-Mason; Tim Cashion; Max Troell; Rosamond L. Naylor; Rahul Agrawal Bejarano; Christopher D. Golden (Proceedings of the National Academy of Sciences, 2026)
Aquaculture, the single fastest growing food sector, is central to achieving key Sustainable Development Goals (e.g., SDG 2: Zero Hunger). Linking the nutrient composition of >2,800 aquatic species with >2 million fishmeal and farmed fish transactions in international aquatic food trade between 2015 and 2019, we examined aquaculture’s nutritional flows and distributional equity. We found that aquaculture provided adequate intakes for nearly a quarter of a million individuals, on average, across 14 key nutrients, and for up to 2.7 billion individuals for several nutrients, such as Vitamin B 12 . The vast majority of these nutrients (76.8%) were domestically retained, contributing to the nutritional security of producer countries. With most internationally traded nutrients originating from nutritionally vulnerable countries (57.7% for fishmeal and 66.3% for farmed aquatic foods), rethinking existing distribution policies with nutrition as the primary objective may help unlock the full potential of aquaculture to eliminate hunger and malnutrition.